Investigating COVID‐19‐Related query logs of Chinese search engine users. Issue 1 (22nd October 2020) - Ye, Ziyi; Mao, Jiaxin; Liu, Yiqun; Zhang, Min; Ma, Shaoping
Abstract: Query logs include valuable information for understanding user intent and behavior in Web search. In this article, we investigate COVID‐19‐related query logs by dividing search sessions into different intent and analyzing the user behavior of groups and individuals. We believe it important to learn about the epidemic's influence on users' search behavior and refine search engine to confront similar epidemic outbreaks in the future.